Anaerobes in ejaculates of subfertile men - Eggert-Kruse, Waltraud; Rohr, Gerhard; Ströck, Wolfram; Pohl, Susanne; Schwalbach, Beate; Runnebaum, Benno (Human reproduction update, 1995)
The clinical significance of micro-organisms in semen samples of asymptomatic subfertile patients is a matter of constant debate. Usually little attention is paid to anaerobic bacteria as they are sensitive to transportation and culturing, and differentiation is difficult, costly and time-consuming. In the present study, special screening was carried out for anaerobes in ejaculates in addition to the routine microbial cultures of genital secretions of both partners. In addition to standard semen analysis and evaluation of sperm ability to penetrate cervical mucus (CM) in vivo (postcoital testing) and in vitro using a standardized test system, semen samples from 126 randomly chosen males of couples with a median duration of infertility of 4 years were examined for colonization with anaerobic bacteria. All couples were without clinical signs or symptoms of genital tract infection. The special care taken for anaerobic growth in semen samples gave a high rate of positive cultures and showed that nearly all ejaculates (99%) were colonized with anaerobic micro-organisms, and potentially pathogenic species were found in 71% of men. This rate was more than four times higher than that obtained with routine cultures and standard transportation (16%). Anaerobic bacterial growth of ≥106 colony forming units (CFU)/ml was seen in 42% (total range 103-108 CFU/ml). In addition, aerobic growth was found in 96%(≥106 CFU/ml in 21%), potentially pathogenic species in 61% of semen specimens. There were no marked differences in the prevalence of anaerobic micro-organisms in patients with reduced or normal sperm count, motility or morphology. Nor was there any significant difference in anaerobic colonization between samples with impaired or good ability to penetrate CM of female partners (in vivo or in vitro), or the CM of fertile donors in the in-vitro sperm-cervical mucus penetration test (SCMPT) in this asymptomatic group of patients. There was no clear association between microbial colonization and subsequent fertility in vivo within an observation period of 6 months. The results of this study suggest that anaerobic bacteria are often not detected when routine methods for microbial evaluation are used. This should be considered during assisted reproduction and in patients with symptoms of genital tract infection and should lead to further studies in infertile patients where subclinical infection or inflammation is indicated by specific markers in semen samples.